From Neo-Kantianism to phenomenology. Emil Lask's revision of transcendental philosophy: Objectivism, reduction, motivation - Ainbinder, Bernardo (2015)
Recently, Emil Lask's work has been the object of renewed interest. As it has been noted, Lask's work is much closer to phenomenology than that of his fellow Neo-Kantians. Many recent contributions to current discussions on this topic have compared his account of logic to Husserl's. Less attention has been paid to Lask's original metaphilosophical insights. In this paper, I explore Lask's conception of transcendental philosophy to show how it led him to a phenomenological conversion. Lask found in Husserl's Logical Investigations the possibility of grounding transcendental philosophy in purely objective terms, thus avoiding any risk of psychologism. But he also concluded that the tools found in Logical Investigations needed to be complemented by a method which would inquire back fr om the constituted to the constituting (anticipating Husserlian reduction) and a way of grounding such a methodological move in experience itself (anticipating Husserlian motivation). Lask then provided a model for reduction and motivation without bringing a transcendental ego into the picture.